Sylvia, Reno County - McCary, Ethan (Kansas State University, The Chapman Center for Rural Studies, 2018)
This study describes the once burgeoning town of Sylvia in Reno County, Kansas. Propelled by local agriculture and a railroad line laid by the Atchison, Topeka, and Santa Fe Company, Sylvia saw impressive growth during the latter half of the 19th century. Once referred to as, "one of the best farming and stock countries in all of Kansas," Sylvia is now witness to a steady decline in population after having peaked at the beginning of the 20th century.
Ethan McCary, “Sylvia, Reno County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/207.
Keywords: Agriculture; Atchison Topeka and Santa Fe Railroad; Kansas; Mill; Reno County; Sylvia